Conflitos religiosos e relações políticas no Pará (1930-1941) - Mendes, Mayara Silva (2006)
This disssertation aimed at discussing religious conflicts and political relations in Pará between 1930 and 1941 against the political background of the events of the 1930 s and of the tenure of Dom Antônio de Almeida Lustosa as bishop of Pará. In this period, some priests have positioned themselves against the political status quo, taking some attitudes that pleased neither the political bosses nor the local catholic hierarchy, which provoked a censure on them. Involved with electoral lawsuits or defalcation of catholic property, Father José Maria do Lago, Father José Foulquier, Father Leandro Pinheiro and Father Alcides Paranhos were forced to rethink their sacerdotal behavior towards society. Working with different kinds of official documents and newspapers, this work discusses the actions of such religious men and the positions and actions of the Catholic Church and of the local Governments concerning these attitudes, which were classified, by some politicians of that time, as petty politics.